2000
DOI: 10.1002/biof.5520110301
|View full text |Cite
|
Sign up to set email alerts
|

Is chromium a trace essential metal?

Abstract: If chromium is an essential metal it must have a specific role in an enzyme or cofactor, and a deficiency should produce a disease or impairment of function. To date, no chromium-containing glucose tolerance factor has been characterized, the purpose of the low-molecular-weight chromium-binding protein is questionable, and no direct interaction between chromium and insulin has been found. Furthermore, chromium3+ is treated like the toxic metals arsenic, cadmium, lead and mercury in animals. Chromium3+ may be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(79 citation statements)
references
References 107 publications
1
77
0
1
Order By: Relevance
“…Approximately 0.4-2.5 % of Cr III is gastrointestinally absorbed (Institute of Medicine 2001), and it must be regarded as the ultimate toxic form of chromium available for metabolism by animal cells (Léonard and Lauwerys 1980;Levina and Lay 2008). Because no chromium deficiency has been consistently reported amongst healthy human populations (Stallings and Vincent 2006;Stearns 2007), the fact of its ''essentiality'' remains a controversial matter (Stearns 2000;Levina et al 2003;Stallings and Vincent 2006). Furthermore, because chromium may accumulate and is possibly genotoxic to animals and humans (Smith 1970;Debetto and Luciani 1988;Snow 1991;Bridgewater et al 1994;Stearns et al 1995;Błasiak and Kowalik 2000), excessive chromium intake (or exposure) should be avoided.…”
Section: Cadmium Lead and Chromium Exposure Assessments For Huntersmentioning
confidence: 99%
“…Approximately 0.4-2.5 % of Cr III is gastrointestinally absorbed (Institute of Medicine 2001), and it must be regarded as the ultimate toxic form of chromium available for metabolism by animal cells (Léonard and Lauwerys 1980;Levina and Lay 2008). Because no chromium deficiency has been consistently reported amongst healthy human populations (Stallings and Vincent 2006;Stearns 2007), the fact of its ''essentiality'' remains a controversial matter (Stearns 2000;Levina et al 2003;Stallings and Vincent 2006). Furthermore, because chromium may accumulate and is possibly genotoxic to animals and humans (Smith 1970;Debetto and Luciani 1988;Snow 1991;Bridgewater et al 1994;Stearns et al 1995;Błasiak and Kowalik 2000), excessive chromium intake (or exposure) should be avoided.…”
Section: Cadmium Lead and Chromium Exposure Assessments For Huntersmentioning
confidence: 99%
“…She did not find a correlation between chromium and GTF activity. Stearns also investigated the issue of the essentiality of chromium to human health, and found that "no chromium-containing glucose tolerance factor has been characterized, the purpose of the low-molecular-weight chromium-binding protein is questionable, and no direct interaction between chromium and insulin has been found" [79]. Moreover, she criticized the dietary supplementation of chromium: "Chromium+3 may act clinically by decreasing the iron stores that are linked to diabetes and heart disease.…”
Section: Grant and Mcmullenmentioning
confidence: 99%
“…Moreover, she criticized the dietary supplementation of chromium: "Chromium+3 may act clinically by decreasing the iron stores that are linked to diabetes and heart disease. This would make chromium+3 a pharmacological agent, not an essential metal" [79].…”
Section: Grant and Mcmullenmentioning
confidence: 99%
“…Isolated strains were grown in M9 medium with 2 mM Cr(VI) at a range of pH values (5,6,7,8,9) at 180 rpm and 37°C. The temperature optimum was determined between 20°C and 42°C (20°C, 28°C, 30°C, 37°C, 42°C) at pH 7.4.…”
Section: Determination Of Ph and Temperature Optimum For Cr(vi) Reducmentioning
confidence: 99%
“…Like most heavy metals, chromium has toxic effects on both humans and environmental organisms [4]. Trace amount of chromium is required for a variety of enzymes [5][6][7], while accumulation in the human body can cause cancer, growth and developmental abnormalities, neuromuscular control defects, renal malfunction, mental retardation and other illnesses [8]. Though chromium exists in varied valance states ranging from Cr(II) to Cr(VI), Cr(III) and Cr(VI) are the most stable forms in nature [9].…”
Section: Introductionmentioning
confidence: 99%